The importance of legal infrastructure for regulation (and deregulation) in developing countries - Ogus, Anthony (Philippine Journal of Public Administration, 2003)
Applications of Western models of regulation and deregulation to developing countries have often been insensitive to whether the legal infrastructure in the recipient country is appropriate to integrate the models. This study addresses the issue of legal infrastructure, first, by reviewing the literature on the relationship between economic growth and legal systems. The predominant view which has emerged is that legal structures, particularly those relating to the "rule of law" have an important influence on economic development and that the failure of attempts to reform those structures, particularly by adopting Western models, has impeded growth. Attempts to eradicate corruption, another fetter on economic performance have also foundered. After an exploration of the concepts of the "rule of law" and corruption in developing countries, explanations are sought for the alleged failures by reference to cultural tensions, political influence, and inappropriate goals formulated by donor institutions and Western commentators.